The influence of Artificial intelligence, Digital leadership on Organizational performance mediated by Innovative work behaviour in the Hotel Industry in Jakarta - Yudhaputri, Egabetha; Willy Arafah; Sarfilianty Anggiani (CV. Media Digital Publikasi Indonesia, 2025)
This study aims to analyse the impact of the role of innovative work behaviour between artificial intelligence and digital leadership on improving organizational performance at hotel industry in Jakarta. This research uses quantitative methods withcross-sectional data collection. This study consists of 8 hotels with a total sample size of 124 respondents. Data were collected using a questionnaire distributed to 124 managerial level leaders at 4-star and 5-star hotels in Jakarta. This research data analysis uses SPPS for descriptive statistics and Structural Equation Modeling (SEM) PLS for hypothesis analysis. The results showed that artificial intelligence and digital leadership does not have a direct effect on organizational performance but with mediation can strengthen the influence so that artificial intelligence and digital leadership has a significant effect on organizational performance. The mediating role of using innovative work behaviour variables in this study has produced research findings that can strengthen the influence of artificial intelligence, digital leadership variables on improving organizational performance in the hotel industry in Jakarta. The managerial implication of this research is that artificial intelligence can be developed into the main management strategy in improving business and increasing literacy and innovative behaviour related to technology both artificial intelligence and other digital skills such as emphasizing digital and innovative culture.